Production process for increasing resistance of heating wire and shortening heating joint
By optimizing the heating wire material formula, adopting a non-circular cross-section design and spiral winding structure, and performing high-temperature oxidation treatment and ceramic coating treatment, the existing heating wire has been solved, and efficient resistance performance and long-term high-temperature stability are achieved.
Patent Information
- Application Number
- CN202411698969.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-07
AI Technical Summary
The cross-sectional design of existing heating wires is mostly circular, resulting in short current path and low resistivity, which cannot meet the needs of high power density. At the same time, the thermal effect distribution is uneven, resulting in local overheating and thermal fatigue problems.
Nickel-chromium alloy or iron-chromium aluminum alloy is used as heating wire material, rare earth elements (such as cerium, yttrium) and grain refinement agents (such as titanium diboride and alumina) are added, and the grains are refined by vacuum induction smelting and electroslag remelting and refining, and microwave annealing is used to refine the grains. At the same time, a non-circular cross-sectional design (such as elliptical, hexagonal) and spiral wound wire structure are adopted to perform high-temperature oxidation treatment and a high-resistance ceramic coating is deposited.
The resistance performance and oxidation resistance of the heating wire are significantly improved, and the resistance path efficiency and thermal effect distribution uniformity are achieved, which extends the service life and improves reliability.
Smart Images

Figure CN119571137A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heating wire production, and in particular to a production process for increasing the resistance of a heating wire and shortening a heating section. Background Art
[0002] The heating wire is a core component widely used in electric heating equipment. It mainly generates heat by passing current through high-resistance materials to provide stable thermal energy. Common heating wire materials include nickel-chromium alloy (NiCr) and iron-chromium-aluminum alloy (FeCrAl), which have good electrical conductivity, mechanical strength and high-temperature oxidation resistance. However, the existing heating wire manufacturing technology mainly focuses on the selection of basic materials and simple surface treatment, which is difficult to meet the performance requirements of modern high-efficiency and energy-saving equipment for heating elements. In the fields of industrial electric furnaces, household appliances, etc., the resistance value of the heating wire, the uniformity of the thermal effect distribution, and the long-term high-temperature stability directly determine the power density and service life of the equipment. There are many deficiencies in the existing technology.
[0003] The resistance value of existing heating wires is generally low, resulting in a long heating section. The cross-section design of traditional heating wires is mostly circular. Although this structure is easy to process, the current path is short and the resistivity is low, which cannot fully meet the needs of high power density. In addition, due to the unoptimized material formula, such as coarse grains and poor alloy uniformity, the conductive properties of the heating wire are often difficult to maintain stable at high temperatures. This inefficient resistance performance not only limits the miniaturization of heating equipment, but also increases energy consumption and reduces overall work efficiency.
[0004] Secondly, the thermal effect distribution of traditional heating wires is often uneven. Conventional geometric processing mostly adopts a single-layer spiral structure or a straight line design. The current distribution in the heating section is uneven, which can easily lead to local overheating and thermal fatigue problems. This phenomenon not only affects the heating efficiency, but also shortens the service life of the heating wire. In addition, the surface structure is single and lacks microscopic design. The thermal conductivity performance of the heating wire has not been fully optimized, which further limits its potential for performance improvement. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a production process for increasing the resistance of the heating wire and shortening the heating wire, which solves the problem that the cross-sectional design of traditional heating wires is mostly circular, but the current path is short, the resistivity is low, and it cannot fully meet the requirements of high power density.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a production process for increasing the resistance of a heating wire and shortening a heating section, comprising the heating wire material being a nickel-chromium alloy or an iron-chromium-aluminum alloy, and comprising the following components:
[0007] Nickel or iron matrix elements, 60% to 80% by weight;
[0008] Chromium element, 20% to 30% by weight;
[0009] Rare earth elements, 0.2% to 0.5% by weight;
[0010] Aluminum element, 4% to 8% by weight;
[0011] The remaining components are other inevitable impurities.
[0012] Preferably, the rare earth elements include cerium (Ce) and yttrium (Y), and their total weight percentage is 0.2% to 0.5%, wherein the mass fraction of cerium is controlled at 0.15% to 0.4%, and the mass fraction of yttrium is controlled at 0.05% to 0.1%; the formula also contains a trace amount of titanium (Ti), and its weight percentage is 0.1% to 0.3%, so as to improve the material's resistance to high-temperature oxidation.
[0013] Furthermore, the heating wire material is a nickel-chromium alloy or an iron-chromium-aluminum alloy, comprising the following components: a nickel or iron matrix element, with a weight percentage of 60% to 80%, the matrix element plays a dominant supporting and conductive role in the material, and provides good high-temperature mechanical properties; a chromium element, with a weight percentage of 20% to 30%, which improves the material's antioxidant properties by generating a dense chromium oxide film at high temperatures, while regulating the material's resistivity and mechanical strength; a rare earth element, with a weight percentage of 0.2% to 0.5%, which further improves the material's long-term stability by adjusting grain boundary characteristics and inhibiting high-temperature oxidation; an aluminum element, with a weight percentage of 4% to 8%, which generates a stable aluminum oxide protective film at high temperatures, improves the material's high-temperature antioxidant properties and enhances its surface thermal stability; the remaining components are other unavoidable impurities, which are controlled to a minimum to ensure the purity of the material and performance consistency. Preferably, the rare earth elements include cerium (Ce) and yttrium (Y), and their total weight percentage is 0.2% to 0.5%, wherein cerium enhances the grain boundary stability of the material and reduces the high-temperature oxidation rate by precipitation at the grain boundaries, and yttrium further improves the creep resistance by increasing the grain boundary strength and improving the uniformity of the microstructure; wherein the mass fraction of cerium is controlled at 0.15% to 0.4%, and the cerium content can optimize the oxidation resistance of the grain boundaries while maintaining the ductility of the alloy, and the mass fraction of yttrium is controlled at 0.05% to 0.1%, and its low doping amount can significantly improve the grain boundary strength and stability at high temperatures; the formula also contains a trace amount of titanium (Ti), and its weight percentage is 0.1% to 0.3%, which refines the grains by forming a dispersed refining phase inside the grains, and at the same time improves the strength and oxidation resistance of the material at high temperatures.
[0014] Preferably, the material further comprises a grain refiner, which is titanium diboride and aluminum oxide, and the addition amount thereof is 0.1% to 0.3%; the grain refiner refines the grains by controlling the grain boundary distribution, so that the average grain size is controlled at 3 to 5 microns.
[0015] Furthermore, the material also contains a grain refiner, which is titanium diboride and aluminum oxide, and the addition amount is 0.1% to 0.3%, and the growth and abnormal growth of grains are inhibited by forming uniformly distributed dispersed particles during the smelting and cooling process; titanium diboride plays a significant role in grain boundary strengthening in the material, and its high melting point and chemical stability ensure that the morphology and distribution of the particles remain stable in a high temperature environment, thereby providing long-term structural stability and mechanical reinforcement effects; aluminum oxide promotes the uniform distribution of grain boundaries through the interface interaction with the substrate metal, while improving the creep resistance and oxidation resistance of the material; the addition amount of the refiner is optimized, and the grain refinement effect can be achieved without significantly changing the ductility and conductivity of the material, and the grain size can be uniformly controlled at 3 to 5 microns by regulating the smelting and annealing processes; the refined grains significantly improve the strength and high-temperature stability of the material, effectively reduce the embrittlement caused by coarse grains, and ensure the uniformity of the material's resistance distribution and thermal fatigue resistance.
[0016] Preferably, the process comprises the following steps:
[0017] Material optimization: the material formula described in claim 1 is subjected to vacuum induction melting and electroslag remelting refining treatment, and after melting, the grains are refined by microwave annealing technology;
[0018] Geometric structure processing: Use high-precision wire drawing dies to process the non-circular cross-section of the heating wire, and use spiral winding equipment to process the spiral structure;
[0019] Surface treatment: The surface of the heating wire is subjected to high-temperature oxidation treatment to form an oxide film, and a high-resistance ceramic coating is deposited to form a composite structure.
[0020] Preferably, the smelting process is controlled within a temperature range of 1650°C to 1750°C, rare earth elements are added in the form of powder or particles in the later stage of smelting, and are kept uniformly distributed by constant temperature stirring; the microwave annealing temperature is controlled within a range of 600°C to 850°C, and the insulation time is 12 hours.
[0021] Further, material optimization: the material formula described in claim 1 is subjected to vacuum induction melting and electroslag remelting and refining treatment, wherein vacuum induction melting removes gas and non-metallic inclusions by heating and stirring the metal raw materials in a vacuum environment, while ensuring the initial uniform distribution of rare earth elements; electroslag remelting further improves the purity and uniformity of the material by heating the molten metal with an electric arc and filtering out impurities and inclusions, and uses high-purity slag to ensure efficient purification reaction of the alloy formation; the smelted alloy is refined by microwave annealing technology, and microwave annealing suppresses abnormal grain growth by uniformly heating the precipitates and grain boundary movement at the grain boundaries, so that the grain size of the material is effectively controlled, while optimizing the grain boundary distribution and strengthening effect; geometric structure processing: a high-precision wire drawing die is used to process the non-circular cross-section of the heating wire cross-section. During the wire drawing process, the die pressure and processing speed are monitored in real time to ensure that the cross-sectional shapes such as elliptical and hexagonal have good processing accuracy and dimensional consistency, and the heating wire is tightly spirally processed by advanced spiral winding equipment, and the winding equipment is equipped with a dynamic adjustment function to adjust the heating wire according to the shape of the cross-section. The target resistance characteristic adjusts the pitch and winding density, thereby increasing the current path length and resistance value; surface treatment: the surface of the heating wire is subjected to high-temperature oxidation treatment to generate a dense oxide film. The oxidation treatment optimizes the structure and thickness of the oxide film through multi-stage temperature control to ensure that the oxide film is evenly attached and has strong bonding force. At the same time, a high-resistance ceramic coating is deposited by a sol-gel method to form a composite structure. The ceramic coating achieves high strength and effective improvement of oxidation resistance through multi-layer deposition and sintering processes; preferably, the smelting process is controlled within a temperature range of 1650°C to 1750°C, within which the matrix elements are fully melted, and the rare earth elements are added in the form of powder or particles in the later stage of smelting to avoid the loss of rare earth elements due to high-temperature volatilization, and the rare earth elements are kept uniformly combined with the matrix through constant temperature stirring; the microwave annealing temperature is controlled within a range of 600°C to 850°C, and the strength and ductility of the material can be balanced through annealing treatment within this range. The annealing holding time is set to 12 hours to ensure uniform migration of grain boundaries and grain refinement, thereby improving the overall performance and stability of the material.
[0022] Preferably, the non-circular cross-sectional shape includes an elliptical, hexagonal or trapezoidal structure, the ratio of the major axis to the minor axis of the ellipse is 1.5:1 to 2:1, and the ratio of the base of the trapezoid is 1.2:1 to 1.5:1; the pitch of the spiral structure is 0.5 to 2 mm, and the coil diameter is controlled at 0.8 to 1.2 mm.
[0023] Furthermore, the non-circular cross-sectional shape includes an elliptical, hexagonal or trapezoidal structure. The non-circular cross-sectional design increases the resistance value by extending the current path, while optimizing the thermal conductivity characteristics of the cross-section to improve the uniformity of heating; the ratio of the major axis to the minor axis of the elliptical cross-section is preferably 1.5:1 to 2:1, which can significantly increase the length of the resistance path while ensuring the feasibility of the processing technology, thereby effectively improving the overall resistance performance; the hexagonal cross-section optimizes the current distribution through a symmetrical design, avoids hot spots caused by excessive local current density, and enhances the mechanical stability of the cross-section; the trapezoidal cross-sectional base ratio is 1.2:1 to 1.5:1, and the current path is further extended by increasing the asymmetry of the cross-sectional shape, optimizing the resistance characteristics, and achieving better thermal diffusion effect through heat distribution from the small side to the large side; the cross-sectional processing adopts high-precision The wire drawing die and real-time dimension monitoring equipment, combined with the technology of dynamically adjusting the die pressure and the wire drawing speed, ensure that the non-circular cross-sectional shape after processing has high precision and good dimensional consistency; the pitch of the spiral structure is 0.5 to 2 mm, and the dynamic adjustment of the pitch is achieved through the precision winding process to meet the design requirements of different resistance values and heating section lengths. The reduction in pitch can increase the winding density per unit length, thereby further improving the resistance value; the coil diameter is controlled at 0.8 to 1.2 mm, and the uniformity of the thermal effect distribution is achieved by optimizing the coil diameter to avoid heat accumulation or uneven power density caused by local coils that are too dense or too loose; the processing of the spiral structure is combined with finite element simulation technology to optimize the current path and thermal distribution of the winding to ensure that the spiral structure achieves uniform distribution of thermal effects while improving the resistance performance.
[0024] Preferably, the high-temperature oxidation treatment includes multi-stage temperature control, the oxidation temperature is gradually increased in the range of 800°C to 1100°C, the oxidation atmosphere is a mixed gas of oxygen and nitrogen, and the ratio is 7:3; the oxide film thickness is controlled at 5 to 10 μm; the ceramic coating is prepared by a sol-gel method, and the coating thickness is 3 to 5 μm.
[0025] Furthermore, the high-temperature oxidation treatment includes multi-stage temperature control, and the oxidation temperature is gradually increased in the range of 800°C to 1100°C, wherein the initial stage of low-temperature oxidation (800°C to 900°C) is used to promote the uniform formation of the oxide film and generate an initial protective film at the grain boundary to enhance the bonding between the film and the substrate, and then the temperature is increased in the intermediate stage (900°C to 1000°C) to further thicken the oxide film and optimize its structural density, and finally in the high-temperature stage (1000°C to 1100°C) the oxide film is stabilized and obtains an ideal thickness and density; the oxidizing atmosphere is a mixed gas of oxygen and nitrogen, and the ratio is preferably 7:3. The precise control of the oxygen ratio can ensure the generation rate and quality of the oxide film, and the addition of nitrogen can reduce the high-temperature corrosion of the substrate during the oxidation process. Risk; The thickness of the oxide film is controlled at 5-10 μm, and the thickness of the oxide film is monitored in real time by online optical interference method to ensure the accuracy and consistency of the oxidation process; The ceramic coating is prepared by a sol-gel method, and the coating achieves complete coverage of the surface of the heating wire through a uniform dipping process in the sol stage. After coating, the sol is gradually gelled during the sintering process when the temperature is gradually increased to 1000°C to form a stable ceramic coating. The thickness of the coating is preferably controlled at 3-5 μm, and the thickness uniformity and structural stability of the coating are ensured by multiple coatings and segmented curing technology. At the same time, through a layered coating design, high-resistance ceramic particles and a thermally conductive protective layer are embedded in the coating to optimize the electrical properties and thermal diffusion capacity of the coating, ultimately forming a composite protective layer structure with excellent antioxidant properties and high-temperature stability.
[0026] Preferably, the surface of the heating wire is provided with a composite protective layer composed of an oxide film and a ceramic coating, and the protective layer has excellent high-temperature performance and can effectively extend the service life.
[0027] Preferably, the oxide film of the surface protection layer is aluminum oxide or chromium oxide, and nanoparticles are embedded in the ceramic coating, including nickel oxide and titanium oxide, wherein the volume fraction of the nanoparticles is 5% to 10%, and the total thickness of the coating is 3 to 10 μm.
[0028] Preferably, the grain size of the heating wire is controlled at 3-5 μm, the cross-section is elliptical or hexagonal, the surface has micro grooves with a depth of 50-200 nm and a nanopore structure with a pore size of 2-10 μm; in a high temperature environment, the resistance value fluctuation range is less than ±5%.
[0029] Furthermore, the surface of the heating wire has a composite protective layer composed of an oxide film and a ceramic coating, and the protective layer is prepared by a multi-stage process, wherein the inner layer is an oxide film and the outer layer is a ceramic coating, and the close combination of the two effectively improves the high-temperature oxidation resistance and thermal stability of the heating wire; the main component of the oxide film is aluminum oxide or chromium oxide, and the thickness and structural density are controlled by multi-stage oxidation during its generation process, which can provide excellent oxygen isolation effect and chemical stability in a high-temperature environment; nanoparticles are embedded in the ceramic coating, including nickel oxide (NiO) and titanium oxide (TiO2), wherein the nanoparticles are distributed in the coating matrix by chemical vapor deposition (CVD) or physical vapor deposition (PVD) technology, and the volume fraction of the nanoparticles is preferably 5% to 10%, which improves the thermal conductivity of the coating while ensuring the oxidation resistance and mechanical stability of the coating; the total thickness of the coating is controlled at 3 to 10 μm, and the thickness uniformity and structural stability are achieved by multi-layer coating and staged sintering process, wherein the bottom layer of the coating is a high-resistance ceramic to enhance the resistance performance, and the middle layer is a heat-resistant ceramic. The material provides high temperature stability, and the outer layer is a thermal conductive protective film to optimize the heat diffusion effect; preferably, the grain size of the heating wire is controlled at 3-5μm, and the grain refinement is achieved through the coordinated vacuum induction melting, electroslag remelting and microwave annealing processes. The refined grains have a uniform distribution characteristic, which effectively improves the mechanical strength and creep resistance of the heating wire; the cross-section of the heating wire is designed to be elliptical or hexagonal, wherein the elliptical cross-section extends the current path through a reasonable ratio of the major axis to the minor axis, and the hexagonal cross-section optimizes the current distribution through a symmetric design, thereby enhancing the uniformity of the heating area; the surface has a micro-groove with a depth of 50-200nm and a nano-pore structure with an aperture of 2-10μm, wherein the micro-groove is processed by a laser texturing process, and the nano-pore is prepared by a plasma etching technology, and the superposition design of the micro-groove and the nano-pore effectively increases the complexity of the surface current path and the thermal conductivity; in a high temperature environment, the resistance value fluctuation range is less than ±5%, and the heating wire maintains stable electrical and mechanical properties under long-term high temperature working conditions, effectively extending the service life and improving reliability.
[0030] The present invention provides a production process for increasing the resistance of a heating wire and shortening a heating section. It has the following beneficial effects:
[0031] 1. The present invention adopts a technical solution of introducing rare earth elements (cerium, yttrium) and grain refiners (such as titanium diboride, aluminum oxide) to optimize the material formula. By improving the grain boundary stability and grain refinement effect of the alloy, the resistance performance and antioxidant ability of the heating wire in a high temperature environment are improved. Compared with the traditional solution in the prior art that does not optimize the alloy formula, the shortcomings of resistance value fluctuation and short service life caused by coarse grains and oxide film failure are solved.
[0032] 2. The present invention adopts a non-circular cross-section design (such as elliptical, hexagonal) and a technical solution for optimizing the spiral winding structure. By extending the current path and improving the structural uniformity of the heating node, a higher resistance path efficiency and uniformity of thermal effect distribution are achieved. Compared with the solution of using circular cross-section heating wires commonly used in the prior art, the problem of low resistance value and uneven heating area caused by too short current path is solved.
[0033] 3. The present invention adopts a technical solution combining high-temperature oxidation treatment and ceramic coating, and significantly enhances the anti-oxidation performance and stability of the heating wire in high-temperature environments by generating a dense oxide film and a composite coating embedded with nanoparticles. Compared with the prior art solution that lacks high-performance coating protection, it solves the problem of resistance attenuation and short service life of the heating wire caused by oxide film peeling and coating failure during long-term use at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Please refer to the attached Figure 1 :
[0037] Example 1: Example of innovative components within the range of values and example of parameters within the range of values in the preparation process
[0038] Specific steps:
[0039] Material preparation:
[0040] The formula is 65% nickel matrix elements, 25% chromium elements, 6% aluminum elements, 0.35% rare earth elements cerium, 0.1% yttrium, and 0.2% grain refiner (TiB2); after the material is melted at 1700°C through vacuum induction melting, rare earth element powder is added and stirred at a constant temperature for 20 minutes, followed by electroslag remelting to improve material uniformity.
[0041] Microwave annealing:
[0042] After smelting, the annealing temperature of the material is set to 750°C, the holding time is 12 hours, and the grain size is controlled to 3-5 μm through annealing.
[0043] Geometry processing:
[0044] Using a high-precision wire drawing die, the heating wire is processed into an elliptical cross-section with a major axis to minor axis ratio of 1.8:1, and then processed into a densely wound spiral structure with a pitch of 1.5mm and a coil diameter of 1mm through a spiral winding device.
[0045] Surface treatment:
[0046] The high-temperature oxidation treatment temperature is increased in three stages (850°C, 950°C, and 1050°C), with an oxygen to nitrogen ratio of 7:3, forming an oxide film with a thickness of 8μm; then the ceramic coating is applied by a sol-gel method, with a sintering temperature of 1000°C and a coating thickness controlled to 4μm.
[0047] Example 2: Examples of innovative components below the range and examples of parameters below the range in the preparation process
[0048] Specific steps:
[0049] Material preparation:
[0050] The formula is 70% nickel matrix elements, 22% chromium elements, 4% aluminum elements, 0.15% rare earth elements cerium, 0.05% yttrium, and 0.1% grain refiner (TiB2); the material melting temperature is 1600°C, and the rare earth elements are added and stirred for 10 minutes without electroslag remelting.
[0051] Microwave annealing:
[0052] The annealing temperature was set at 600°C, the holding time was 6 hours, and the grain size was about 6 to 8 μm.
[0053] Geometry processing:
[0054] The elliptical cross-section was processed using an ordinary wire drawing die, with a major axis to minor axis ratio of 1.3:1, and no spiral structure design was performed.
[0055] Surface treatment:
[0056] The high-temperature oxidation treatment temperature is 800°C, the ratio of oxygen to nitrogen is 5:5, the oxide film thickness is 3μm; the ceramic coating thickness is 2μm, and the sintering temperature is only 900°C.
[0057] Example 3: Examples of innovative components with values higher than the range and examples of parameters in the preparation process with values higher than the range
[0058] Specific steps:
[0059] Material preparation:
[0060] The formula is 60% nickel matrix elements, 30% chromium elements, 8% aluminum elements, 0.5% rare earth elements cerium, 0.2% yttrium, and 0.3% grain refiner (TiB2); the material melting temperature is 1800°C, the stirring time is 40 minutes, and the electroslag remelting time is extended to 1 hour.
[0061] Microwave annealing:
[0062] The annealing temperature was set at 850°C, the holding time was 15 hours, and the grain size was about 2 μm.
[0063] Geometry processing:
[0064] It is processed into a hexagonal cross-section and uses high-precision winding equipment for multi-dense winding design, with a pitch of 0.8mm and a coil diameter of 1.2mm.
[0065] Surface treatment:
[0066] The high-temperature oxidation treatment was increased in stages (900°C, 1000°C, 1100°C), the ratio of oxygen to nitrogen was 8:2, the oxide film thickness was 12μm; the ceramic coating thickness was 6μm, and the sintering temperature was 1100°C.
[0067] Summary: The formula and process parameters of Example 1 are within the recommended range of the innovative point, and show excellent comprehensive performance, including significantly improved weather resistance, mechanical strength and resistance stability, which proves the effectiveness of the technical solution of the present invention in balancing material properties and processing stability; Example 2 shows a significant decrease in performance by reducing the content of innovative components and processing parameters, which is specifically manifested in the reduction of mechanical properties due to coarse grains, poor quality of oxide film and increased fluctuation of resistance value, verifying the sensitivity of the critical values of components and process parameters to performance; Example 3 further optimizes the performance by improving the innovative components and processing parameters, and the weather resistance and mechanical strength reach a higher level, but the processing complexity and cost increase caused by excessively thick oxide film and ultra-fine grains indicate the need to make a reasonable trade-off between performance and economy.
[0068] Comparative Experimental Design
[0069] Experimental objectives
[0070] By comparing the differences between the present invention and the prior art in terms of resistance performance, antioxidant ability, resistance path efficiency, thermal effect distribution uniformity, and high-temperature stability, the technical advantages of the present invention in component design and process optimization are verified.
[0071] Comparative experiment 1: Comparison between the prior art solution lacking innovative component 1 (rare earth element) and the technical solution of the present invention
[0072] Experimental content
[0073] Technical solution of the present invention: Example 1 (containing 0.35% of rare earth elements cerium and 0.1% of yttrium).
[0074] Comparative Example 1: No rare earth element is added in the prior art, and other formulas and process conditions are the same as those in Example 1.
[0075] Test items
[0076] Resistance performance(Ω)
[0077] Antioxidant capacity (oxidation film integrity score, 1 to 10 points)
[0078] Change of oxide film thickness during high temperature operation (μm)
[0079] Resistance stability (percentage change after 1000 hours of operation, %)
[0080] Experimental results table
[0081]
[0082]
[0083] Experimental analysis
[0084] The introduction of rare earth elements significantly improved the resistance performance (increased by 50%) and antioxidant ability (score increased by 80%), and maintained the stability of the oxide film under high-temperature working conditions (thickness change reduced by 86.7%). At the same time, the stability of the resistance value was significantly improved. After 1000 hours of operation, the resistance change was only 1.5%. In the control group, the grain boundary instability and oxide film degradation caused by the lack of rare earth elements caused the resistance fluctuation to reach 8%.
[0085] Comparative experiment 2: Comparison between the prior art solution lacking innovative component 2 (grain refiner) and the technical solution of the present invention
[0086] Experimental content
[0087] Technical solution of the present invention: Example 1 (containing 0.2% titanium diboride as a grain refiner).
[0088] Comparative Example 2: In the prior art, no grain refiner was added, and other formulations and process conditions were the same as those in Example 1.
[0089] Test items
[0090] Resistive path efficiency (resistance per unit length, Ω / m)
[0091] Thermal effect distribution uniformity (heat distribution temperature difference, ℃)
[0092] High temperature thermal fatigue resistance (crack length change after 100 cycles, μm)
[0093] Experimental results table
[0094]
[0095] Experimental analysis
[0096] The addition of grain refiner increased the current path efficiency by 50%, significantly reduced the unevenness of heat distribution (temperature difference reduced by 67%), and showed excellent performance in high-temperature thermal fatigue tests, with crack growth of only 5μm, while the control group had significant crack expansion (growth of 20μm) due to coarse grains, proving the contribution of grain refiner to resistance path optimization and thermal stability.
[0097] Comparative Experiment 3: Comparison of the existing technology and the process of the present invention in the preparation process
[0098] Experimental content
[0099] Technical solution of the present invention: Example 1 (combination of multi-stage oxidation treatment and ceramic coating).
[0100] Comparative Example 3: The prior art adopts a single-stage oxidation treatment without ceramic coating treatment, and the other formulations are the same as those in Example 1.
[0101] Test items
[0102] High temperature stability (1000℃ operation time, h)
[0103] Antioxidation performance (change in oxide film thickness, μm)
[0104] Surface microstructure retention rate (surface groove depth and porosity change, %)
[0105] Experimental results table
[0106]
[0107] Experimental analysis
[0108] The combination of multi-stage oxidation treatment and ceramic coating significantly extends the high-temperature stability (operating time extended by 316%). At the same time, the thickness change of the oxide film in a high-temperature environment is reduced by 90%, and the micro-surface structure retention rate is as high as 98%. The control group had a surface structure that was severely degraded due to single-stage oxidation and lack of ceramic coating protection, with a retention rate of only 60%.
[0109] Summarize
[0110] The contribution of rare earth elements to electrical resistance and antioxidant capacity;
[0111] Rare earth elements significantly enhance resistance performance and anti-oxidation ability by improving grain boundary stability and oxide film formation, especially in high temperature environments, where thickness variation and resistance fluctuation are greatly reduced.
[0112] Optimization of path efficiency and thermal fatigue resistance by grain refiners;
[0113] Grain refiners significantly improve the resistance path efficiency and uniformity of thermal effect distribution, while enhancing thermal fatigue resistance and reducing crack propagation.
[0114] Improvement of high temperature stability and structural retention rate by preparation process
[0115] The multi-stage oxidation treatment and ceramic coating process of the present invention effectively prolongs the high-temperature operating life, improves the uniformity and stability of the oxide film, and maintains the integrity of the surface microstructure.
[0116] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A production process for increasing the resistance of a heating wire and shortening a heating section, characterized in that: The heating wire material is a nickel-chromium alloy or an iron-chromium-aluminum alloy, and contains the following components: Nickel or iron matrix elements, 60% to 80% by weight; Chromium element, 20% to 30% by weight; Rare earth elements, 0.2% to 0.5% by weight; Aluminum element, 4% to 8% by weight; The remaining components are other inevitable impurities.
2. A production process for increasing the resistance of a heating wire and shortening a heating section according to claim 1, characterized in that: The rare earth elements include cerium (Ce) and yttrium (Y), and their total weight percentage is 0.2% to 0.5%, wherein the mass fraction of cerium is controlled at 0.15% to 0.4%, and the mass fraction of yttrium is controlled at 0.05% to 0.1%; the formula also contains a trace amount of titanium (Ti), and its weight percentage is 0.1% to 0.3%, so as to improve the material's resistance to high-temperature oxidation.
3. The production process of increasing the resistance of the heating wire and shortening the heating section according to claim 1, characterized in that: The material also contains a grain refiner, which is titanium diboride and aluminum oxide, and the addition amount thereof is 0.1% to 0.3%. The refiner refines the grains by controlling the grain boundary distribution, so that the average grain size is controlled within 3 to 5 microns.
4. A production process for increasing the resistance of a heating wire and shortening a heating section according to claim 1, characterized in that: The process comprises the following steps: Material optimization: the material formula described in claim 1 is subjected to vacuum induction melting and electroslag remelting refining treatment, and after melting, the grains are refined by microwave annealing technology; Geometric structure processing: Use high-precision wire drawing dies to process the non-circular cross-section of the heating wire, and use spiral winding equipment to process the spiral structure; Surface treatment: The surface of the heating wire is subjected to high-temperature oxidation treatment to form an oxide film, and a high-resistance ceramic coating is deposited to form a composite structure.
5. The production process of increasing the resistance of the heating wire and shortening the heating section according to claim 1, characterized in that: The smelting process is controlled within a temperature range of 1650° C. to 1750° C., rare earth elements are added in the form of powder or particles in the later stage of smelting, and are kept evenly distributed by constant temperature stirring; the microwave annealing temperature is controlled within a range of 600° C. to 850° C., and the insulation time is 12 hours.
6. The production process of increasing the resistance of the heating wire and shortening the heating section according to claim 1, characterized in that: The non-circular cross-sectional shape includes an elliptical, hexagonal or trapezoidal structure, the ratio of the major axis to the minor axis of the ellipse is 1.5:1 to 2:1, and the ratio of the base of the trapezoid is 1.2:1 to 1.5:1; the pitch of the spiral structure is 0.5 to 2 mm, and the coil diameter is controlled at 0.8 to 1.2 mm.
7. The production process for increasing the resistance of the heating wire and shortening the heating section according to claim 1, characterized in that: The high-temperature oxidation treatment includes multi-stage temperature control, the oxidation temperature is gradually increased in the range of 800°C to 1100°C, the oxidation atmosphere is a mixed gas of oxygen and nitrogen, and the ratio is 7:3; the oxide film thickness is controlled at 5 to 10 μm; the ceramic coating is prepared by a sol-gel method, and the coating thickness is 3 to 5 μm.
8. The production process of increasing the resistance of the heating wire and shortening the heating section according to claim 1, characterized in that: The surface of the heating wire is provided with a composite protective layer composed of an oxide film and a ceramic coating. The protective layer has excellent high-temperature performance and can effectively extend the service life.
9. The production process of increasing the resistance of the heating wire and shortening the heating section according to claim 1, characterized in that: The oxide film of the surface protection layer is aluminum oxide or chromium oxide, and nanoparticles including nickel oxide and titanium oxide are embedded in the ceramic coating, wherein the volume fraction of the nanoparticles is 5% to 10%, and the total thickness of the coating is 3 to 10 μm.
10. The production process of increasing the resistance of the heating wire and shortening the heating section according to claim 1, characterized in that: The grain size of the heating wire is controlled at 3-5 μm, the cross section is elliptical or hexagonal, the surface has micro grooves with a depth of 50-200 nm and a nanopore structure with a pore size of 2-10 μm; in a high temperature environment, the resistance value fluctuation range is less than ±5%.
Citation Information
Patent Citations
A tube and a method of manufacturing a tube
CN109072369A
Electrothermal alloy and preparation method thereof
CN109402342A
Production method of barium cleaning iron-chromium-aluminum alloy
CN113337783A
